2019
DOI: 10.1111/jocn.14786
|View full text |Cite
|
Sign up to set email alerts
|

Teaching nurses to teach: A qualitative study of nurses’ perceptions of the impact of education and skills training to prepare them to teach end‐of‐life care

Abstract: Aims and objectives To explore nurses’ perceptions of the impact of a programme designed to train them to teach end‐of‐life care. Background Central to national and international policies are the need for generalist healthcare staff to have education in end‐of‐life care. Much end‐of‐life care education is provided by specialist nurses who often have no specific education development to prepare them to teach. To address this gap, an Education Development Programme (EDP) was developed and delivered to specialist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…With regard to demographic and work-related factors, we found that a higher working position was positively related to behavior toward EOL care. Specialist nurses and nursing group leaders had higher scores in total caring behavior, possibly because they are appropriately trained, have better professional knowledge, and know how to deliver high-quality EOL care [34]. A research also showed that post and title were significant factors to behaviors toward EOL care [35].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to demographic and work-related factors, we found that a higher working position was positively related to behavior toward EOL care. Specialist nurses and nursing group leaders had higher scores in total caring behavior, possibly because they are appropriately trained, have better professional knowledge, and know how to deliver high-quality EOL care [34]. A research also showed that post and title were significant factors to behaviors toward EOL care [35].…”
Section: Discussionmentioning
confidence: 99%
“…Deciding to withhold or withdraw treatment or advanced care planning are two of the most common end-of-life care challenges that cause ethical dilemmas [ 24 , 29 ]. Jack et al stated that most nurses need more confidence in their knowledge and skills in fulfilling their ethical obligations in this field and feel the need for more training [ 43 ]. Also, O’Shea et al emphasized the consideration of laws and policies of societies and countries in the design of educational programs, especially in ethical and legal aspects [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need for improvement in SS demonstrates how essential the constant search for updates and training related to their communication and relational skills is. Appropriately trained nurses are better able to teach their team to provide qualified care that meets users’ and families’ health needs ( 12 ) .…”
Section: Discussionmentioning
confidence: 99%